Talking with strangers: towards a Christian, postmodern, academic model for biblical interpretation - Latham, Roger Allonby (2006)
Postmodernism in Biblical Studies is characterised by proliferation of methodological and ideological interpretive perspectives, emphasis upon the ethics of interpretation and awareness of the role of interpretive communities. Following Stephen E. Fowl, the underlying motives of interpreters can be understood when approaches are analysed in terms of interpretive interests. The work of David J. A. Clines, J. Cheryl Exum and Stephen D. Moore reveals a strong de-confessional motive and a desire to exclude confessional concerns from academic interpretation. This position is ideologically driven and, in terms of liberal academic values, self-contradictory. The difficulties posed for Christian interpretation by the postmodern context are evident in the narrative criticism of Mark Allan Powell and R. Alan Culpepper, where unresolved conflict of theological, methodological and political interests threatens the coherence of the approach. Recent work by Powell addresses postmodern concerns, but fails adequately to engage theoretical and theological issues. A postmodern understanding of the Bible as Christian scripture which affirms both the validity and legitimacy of multiple interpretive perspectives and a pneumatological understanding of the Bible as the Word of God can be framed using the work of Kevin J. Vanhoozer, Stephen E. Fowl, Roman Jakobson and Daniel Patte. Socio-pragmatic objections to the legitimacy and validity of Christian interpretation beyond the faith community can be resisted by asserting a dialogical relationship between the Bible, the church and the wider academic community, and by following Francis Watson’s argument that the church’s discourse is derived from that of the wider society in which it exists. Christian interpretation will seek to engage constructively with other interpretive approaches. A Christian ethics of interpretation characterised by openness, humility, repentance and forgiveness offers a positive contribution to the culture of postmodern academic interpretation. Jesus’ encounter with the Syrophoenician woman in Mark 7 offers a paradigm for such interpretive practice.